(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides some reflections on the political life of the Fergana Valley at the beginning of the 17th century. On the basis of primary sources of that period and literature, relevant topics, the fact that the valley has turned into a disputed region between Ashtarkhanids and Kazakhs is critically analyzed.